1977
DOI: 10.1055/s-0029-1230701
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage in mouse embryos exposed to 1 rad X-rays or negative pions

Abstract: Pregnant mice of two different strains (F/A and NMRI) were exposed to 1 rad of whole-body pion- or X-irradiation at day 8 of gestation. Lucanthone (Miracil D), a known radiosensitizer in various biological systems, was applicated 30 min before irradiation. Five days after treatment the fetuses were observed for developmental anomalies. In both strains of mice it was found that the radiation dose as low as 1 rad results in a significant increase in the rate of abnormal fetuses compared to nonirradiated, but res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The data presented here show a RBE value of 1.6 at 50% malformation which is in good agreement with our previous results of peak pions from the single beam [2]. In contrast to our former data with 1 rad, qualitatively different teratogenic effects between X-rays and pions were observed at higher doses.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The data presented here show a RBE value of 1.6 at 50% malformation which is in good agreement with our previous results of peak pions from the single beam [2]. In contrast to our former data with 1 rad, qualitatively different teratogenic effects between X-rays and pions were observed at higher doses.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies with mouse embryos showed that low level exposures, even to 1 rad, may have a significant deleterious influence on prenatal development [2]. Moreover, potentiating effects with different chemicals and drugs could be demonstrated in the embryonic system of rats and mice.…”
Section: Discussionmentioning
confidence: 97%
“…Prenatal LDIR exposure induces teratogenesis and mortality [5561] (Table 5). In female CF1 and BALB/c strain mice, irradiation with X-rays (100 mGy) at 7 h post fertilization resulted in increased frequency of malformed fetuses and Dwarfism occurrence when examined 18 days later.…”
Section: Ldir and Ldrir-induced Bionegative Effects In Animal Modelsmentioning
confidence: 99%
“…When entire oviducts and uteri were examined at 6 and 24 h after irradiation for signs of very early embryos, observations of delayed first cleavage and increase in the number of abnormal embryos were made, suggesting that the newly fertilized egg was probably the most radiosensitive cell in the mouse [63]. Subjecting pregnant mice from two different strains (F/A and NMRI) to 10 mGy of whole-body pion- or X-ray irradiation at Day 8 of gestation resulted in a significant increase in the rate of abnormal fetuses compared with non-irradiated, but restrained fetuses [55]. When pregnant Swiss albino mice were exposed to low doses of X-rays (~9 mGy) on gestational Day 3.5 (pre-implantation period), Day 6.5 (early organogenesis period) or Day 11.5 (late organogenesis period), and the fetuses were examined on the 18th day of gestation, a significant increase in prenatal mortality was observed for those exposed at 3.5 days post coitus (d.p.c.).…”
Section: Ldir and Ldrir-induced Bionegative Effects In Animal Modelsmentioning
confidence: 99%
“…We are using this phase for the comparison of the effect from different radiation qualities (Mindek et al, 1975). These investigations are part of the preclinical program including experiments on different biological systems as animals, tissues and cells Michel and Fritz-Niggli, 1977). These investigations are part of the preclinical program including experiments on different biological systems as animals, tissues and cells Michel and Fritz-Niggli, 1977).…”
Section: Introductionmentioning
confidence: 99%